Iluminação por combinação de cores: modelo de obtenção das proporções entre os fluxos luminosos via centros de gravidade aplicado ao diagrama de cromaticidade - Assmann, Gustavo Rodrigo Kerkhoff (2023)
This work presents a study on color-mixed LED lighting applied to white light generation, bringing the main perspectives, challenges, and benefits of this technology compared to phosphorcoated LEDs. Radiometric, photometric, and colorimetric concepts involved in color mixing light production are investigated. An LED model composed of four emitters on a single chip is chosen as an object of study and then characterized regarding its electrical current, operating temperature, and luminous flux. Based on the CIE 1976 UCS chromaticity diagram a representation model is proposed, which translates into geometric relationships the color-mixing principles between the emitters of a hypothetical luminaire. Based on this model, and the center of gravity rule applied to the chromaticity diagram, an algorithm able to estimate the proportions between the luminous fluxes of the colors, and their corresponding electric currents, is implemented, in order to meet a light output target defined by chromaticity and luminous flux. Validation tests of this methodology are conduced, confirming its operation principles and applicability for luminaires composed of up to four colors under specific conditions.